humanitas : et condition humaine. - Musée André Malraux, Le Havre (Le Havre : Musée André Malraux, 1988)
Bervoets, Fred ; Cox, Jan ; Dupont, Veerle ; Maieu, Frank ; Mara, Pol ; Pas, Wilfried ; Van Hoeydonck, Paul ; Vanriet, Jan
humanitas : et condition humaine, Musée André Malraux, Le Havre, 3.9. - 18.9.1988
boek